Use of non-conventional medicines by cancer patients - Tenti, Elena; Casedei Gardini, Andrea; Nanni, Oriana; Foca, Flavia; Cumero, Sebastiano (European Journal of Oncology and Environmental Health, 2015)
Background: The number of cancer patients undergoing anticancer treatment who concomitantly take non-conventional medicines is increasing. Among cancer patients the use of non-conventional medicines, often in the form of self-medication, is intended to counteract the side-effects of cancer treatment, alleviate symptoms or strengthen the immune system. Aim of the work: The present study aimed to evaluate how widespread the practice is and to identify the possible interactions between non-conventional medicines and cancer therapies. Methods: This research was an observational prospective study of about 10 weeks. One hundred and forty-three patients undergoing cancer treatment in our day hospital were interviewed about their use of non-conventional medicines. Results: 35.7% (51/143) of patients reported taking vitamin or mineral supplements, 22.4% (32/143) take medicinal herbs and 4.9% (7/143) homeopathic remedies. 75% (24/ 32) using medicinal herbs were